MODEL ANALYSIS OF LEADERSHIP AND WORK DISCIPLINE AGAINST REVENUE SERVICE PERFORMANCE IMPROVEMENT - Yohanson, A K (Prosiding International conference on Information Technology and Business (ICITB), 2015)
In serving employees are expected to carry out all thetasks that have been given with full responsibility, and isalso expected to have a high loyalty and dedication inpractice no exception for apparatus or employees whoserve in the community. The dynamics of a very diversecommunity today demanded that the apparatus / employeein order to work optimally in providing services to thepublic. Implementation of a breakthrough in efforts toexpand the authority to explore sources of revenue shouldbe directed as much as possible for the benefit of theregion and the efforts that led to improved quality ofhuman resources should be based on the proportionality ofthe capabilities and acceptability continue. Not only that,the efforts of others to do as directing employees to theprofessionalism in terms of appropriate staffing agencyneeds gradually and surely must be based on objectivityand proportionality of the capabilities and acceptabilityauthorities concerned to accelerate the achievement oforganizational goals.